Humanity in Mulk Raj Anand’s Novels (Pursuits: A Journal of English Studies, 2022)
This paper discusses about the humanity appeared in the Mulk Raj Anand’s novels specially Untouchable and Coolie. Mulk Raj Anand is extremely outstanding as an Indian novelist, reformer, recognized essayist, craftsmanship commentator, editorial manager, a short story author, columnist, and political lobbyist. Anand is accepted by several critics along with Raja Rao, R.K. Narayan and Ahmed Ali, as one of the India's best writers. A writer’s views and attitudes are floored by a number of ways which work upon him since the childhood to funeral. In this sense, Mulk Raj Anand has no exception to it at all. His cultural, social, academic heritage altogether shapes his art, culture and personality as well. A champion of the poor classes in India, Mulk Raj Anand attacks religious bigotry and established institutions in his numerous novels and short stories. This basic philosophy mixed humanism and socialism into the concept of "bhakti". Anand's devotion to socialism and humanism has had a dual effect on his writing. His humanism lends more artistry to the value of his work, while his belief in socialism tends to reduce from their literacy worth. Anand's earlier novels show a sense of horror and disgust against social and economic ills, the novels of the middle period show a greater concern for and with the human heart. It is, however, in the later novels that a healthy combination of the social and personal concerns is achieved. Thus, the art of Anand, gradually gains much in confidence. While the later novels keep the passion for social justice, they sound greater emotional depths. Anand's short stories suffer from problems. Similar to those in his novel. For his realistic portrayals of the social and economic problems suffered by Indians at the hands of British, as well those of other richer and powerful Indians. In exposing the limitations of tradition, Anand’s mood is in fact ruthful, resentful, ironical and satirical, as the subject and the condition demand. Common themes in the Anand’s novels are religious bigotry, hypocrisy, feudal system, east-west encounter, the place of woman in the society, superstitions, poverty, sufferings, misery, hunger and exploitation.